Comparison between private and public D.El.Ed colleges of Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Education Commission of 1964-66 and the National Policy on Education of 1986 have both prioritised the persistent matter of improving education. Consequently, measures have been implemented to address this matter in an efficient manner.The study comprised a sample size of 72 participants, which consisted of 36 lecturersassistant professors from DIETs (District Institutes of Education and Training) and an additional 36 lecturersassistant professors from private institutes. Interviews were conducted with all participant groups. There is a total of 81 students and 81 parents, with 9 students and 9 parents each representing 9 District Institutes of Education and Training (DIETs), in addition to 9 private institutes located in Delhi. The Cronbach's alpha test is initially utilised to evaluate the reliability of the variable.The study utilises descriptive statistical tools to analyse the scaled variable, while natural language processing is employed to evaluate the responses obtained from the open-ended questionnaire. Based on the analysis conducted, it is evident that a comprehensive range of facilities is consistently available at a 100 rate across all institutions. Nevertheless, there are certain areas where specific facilities are deficient.